Breve nota crítica sobre a introdução da expressão “património intangível” em Portugal - Ramos, M. J. (2005)
UNESCO has formalized, in 1972, a too restrictive view of the concept of “cultural heritage”. This has led, by inversion, to the questionable development of the “immaterial (or intangible) cultural heritage” as an independent tool in international classification processes. This dichotomy entails misunderstandings, which in the Portuguese case were amplified by the fact that there was a conspicuous lack of a criticai multidisciplinary debate, prior to its inclusion in national law and as a theme ín policies of regional assertion.